Effect of Oxygen Flow Rate on the Optical, Electrical, and Mechanical Properties of DC Sputtering ITO Thin Films - Chuen-Lin Tien; Hong-Yi Lin; Chih-Kai Chang; Chien-Jen Tang (Advances in Condensed Matter Physics)
This study presents the effect of oxygen flow rate on the optical, electrical, and mechanical properties of indium tin oxide (ITO) thin films prepared by the DC magnetron sputtering technique. The oxygen flow rate was varied from 10 to 50 sccm. The ITO thin films deposition under different oxygen flow rates exhibits different properties. We used an optical spectrometer to measure the optical transmittance and a four-point probe instrument to determine the resistivity. A home-made Twyman-Green interferometer was used to evaluate residual stress and a microscopic interferometer was used to measure the surface roughness of ITO thin films. The experimental results show that the average optical transmittance is larger than 85% in visible range; the electrical resistivity has a minimum 6.85×10-4 ohm-cm for the oxygen flow of 10 sccm. The residual stress is varied from −0.15 GPa to −0.34 GPa in the range of 10–50 sccm. The root-mean-square (rms) surface roughness is changed from 2.64 nm to 2.74 nm as the oxygen flow rate increases. The results show that the oxygen flow rate has significant influence on the electrical resistivity, residual stress, and surface roughness of the ITO thin film.